Research handbook on biodiversity and law - Bowman, Michael 1950-; Davies, Peter G. G. 1963-; Goodwin, Edward (Research handbooks in environmental law, 2016)
This wide-ranging and comprehensive Handbook examines recent developments in international environmental law (IEL) and the crossover effects of this expansion on other areas of international law, such as trade law and the law of the sea. The expert contributors offer analyses of foundational issues in IEL, such as responsibility for environmental damage, sustainable development and the precautionary principle, alongside studies in topical subject areas including marine protection and the law of international watercourses. This Research Handbook offers an in-depth analysis of IEL, both as a fie